2014
DOI: 10.11604/pamj.2014.18.107.3678
|View full text |Cite
|
Sign up to set email alerts
|

Plasma homocysteine and B vitamins levels in Nigerian children with nephrotic syndrome

Abstract: IntroductionAvailable data on plasma homocysteine level in patients with nephrotic syndrome (NS) are controversial with increased, decreased and unchanged values reported. Therefore, plasma homocysteine and serum B vitamins in Nigerian children with NS were assessed in this studyMethodsFasting blood samples were analysed for plasma homocysteine, serum folate and B vitamins in 42 children with NS and 42 age and sex-matched healthy controls in this case control study. Data were compared between NS and control us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…Inversely, folate levels were significantly lower (p < 0.01) in children affected by chronic renal failure (9.9 nmol/L) than in controls (13.5 nmol/L). The authors [110] found a higher prevalence of HHcy in dialyzed children than in nondialyzed patients (87% vs. 35%), and higher levels of HHcy in dialyzed children with MTHFR mutations (28.5 µmol/L) compared to nondialyzed patients with the mutation (10.7 µmol/L p < 0.002). Child patients (n = 12, aged 11.0 ± 3.5) with acute glomerulonephritis had higher Hcy levels (from 9.4 ± 3.3 to 13.5 ± 2.8 µmol/L) compared to controls (n = 15, 8.4 ± 2.4 µmol/L) and lower vitamin B6 and RBC folate levels (p < 0.01) [104].…”
Section: Hhcy and Renal Diseasesmentioning
confidence: 91%
See 1 more Smart Citation
“…Inversely, folate levels were significantly lower (p < 0.01) in children affected by chronic renal failure (9.9 nmol/L) than in controls (13.5 nmol/L). The authors [110] found a higher prevalence of HHcy in dialyzed children than in nondialyzed patients (87% vs. 35%), and higher levels of HHcy in dialyzed children with MTHFR mutations (28.5 µmol/L) compared to nondialyzed patients with the mutation (10.7 µmol/L p < 0.002). Child patients (n = 12, aged 11.0 ± 3.5) with acute glomerulonephritis had higher Hcy levels (from 9.4 ± 3.3 to 13.5 ± 2.8 µmol/L) compared to controls (n = 15, 8.4 ± 2.4 µmol/L) and lower vitamin B6 and RBC folate levels (p < 0.01) [104].…”
Section: Hhcy and Renal Diseasesmentioning
confidence: 91%
“…HHCy in renal diseases shows a similar pattern to atherosclerosis, i.e., production of lipid-laden macrophage, presence of cholesterol and cholesterol ester, intima thickening, elastic lamina disruption, and luminal platelet accumulation [108,109]. Nephrotic syndrome (NS), a common pediatric kidney disease, is associated with HHCy due to inhibition of the homocysteine remethylation process or disruption in cysteine clearance [110]. Most NS patients are resistant to steroid treatments and have evolved into focal segmental glomerulosclerosis (FSGS) due to the pathogenic effect of HHcy, which causes podocyte injury and glomerulosclerosis [111,112].…”
Section: Hhcy and Renal Diseasesmentioning
confidence: 99%
“…However, we can infer that this abnormal increase may have been a reactional increase related to steroid use to treat NS, similar to the treatment of polymyalgia rheumatica [30]. After the use of vitamin B6, B12 and folic acid in the same patient group, the homocysteine concentrations decreased again [30,31]. Although another study showed that homocysteine concentrations were low during the proteinuria phase, they normalized during remission at 12 weeks and 1 year.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, a previous study showed an increase in Hcy levels and decreased vitamin B12 levels in 42 children with NS in Nigeria. 9 Hyperhomocysteinemia in NS patients was suggested to be associated with an inhibition of the homocysteine remethylation process or disruption in cysteine clearance. 9 The normal homocysteine value in adults is 5-15 µmol/L, but there is no consensus on normal levels in children.…”
Section: Discussionmentioning
confidence: 99%
“…9 Hyperhomocysteinemia in NS patients was suggested to be associated with an inhibition of the homocysteine remethylation process or disruption in cysteine clearance. 9 The normal homocysteine value in adults is 5-15 µmol/L, but there is no consensus on normal levels in children. 10 Naseri et al in his study on Hhcy in children and young adults on dialysis, defined it in children by age: >8.3 µmol/L for children aged 2-10 years, >10.3 µmol/L for children aged 10-15 years, and >11.3 µmol/L for children aged 15-18 years.…”
Section: Discussionmentioning
confidence: 99%